Modeling and investigation of deformation kinetics in polymer adhesive systems - Pustovoitova, O.; Пустовойтова, Оксана (Харківський національний автомобільно-дорожній університет, 2025)
The article studies the change in the elastic limit and tensile strength of acrylic adhesive over time - from the maximum value (short-term strength) to the minimum (long-term strength limit). The development of deformations in samples under constant loads ranging from 0.2 to 0.85 of the destructive ones was experimentally studied. It is shown that at stresses below the long-term strength limit, the deformation curve includes two sections: instantaneous deformations and viscous deformations that develop over time. Destruction occurs due to the accumulation of damage (cracks, defects), and its speed depends on the stress level and the configuration of the adhesive joint. Purpose. The aim of this study is to establish the patterns of change in the yield strength and ultimate strength of acrylic adhesive over time under sustained loading, as well as to analyze the damage accumulation process in adhesive joints depending on stress level. Methodology. The experimental research involved testing acrylic adhesive specimens under constant loads ranging from 20% to 85% of their short-term (ultimate) strength. The development of deformations over time was observed, and the nature of failure was recorded. Results. It was found that under stresses below the long-term strength limit, the deformation curve consists of two distinct regions: instantaneous (elastic) deformation and time-dependent (viscous) deformation. Failure occurs due to the progressive accumulation of micro-damage, including cracks and defects. The rate of degradation depends on both the stress level and the geometry of the adhesive joint. Originality. This work provides a comprehensive description, for the first time, of the transition from short-term to long-term strength of acrylic adhesive under constant loading, taking into account the influence of joint configuration on the failure rate. Practical value. The results can be applied to predict the durability of adhesive joints in structures operating under sustained loads, such as anchor systems, and to optimize joint geometry in order to improve reliability.
Моделювання та дослідження кінетики деформацій у полімерних клейових системах
Keywords: creep; acrylic adhesive; polymer adhesive system; short-term strength; ultimate strength; deformations; construction joints; повзучість; акриловий клей; полімерна клейова система; короткочасна міцність; межа тривалого опору; деформації; будівельні з'єднання; 629.341; 10.30977/AT.2219-8342.2025.56.0.06